2022
DOI: 10.1371/journal.pone.0262880
|View full text |Cite
|
Sign up to set email alerts
|

Long-term glycemic variability and the risk of mortality in diabetic patients receiving peritoneal dialysis

Abstract: Background The large amount of glucose in the dialysate used in peritoneal dialysis (PD) likely affects the glycemic control. The aim of this study was to investigate the association between HbA1c variability, as a measure of long-term glycemic variability, and the risk of all-cause mortality in diabetic patients with PD. Methods 325 patients with diabetes and ESRD were followed (2008–2018) in the Swedish Renal Registry. Patients were separated in seven groups according to level of HbA1c variability. The gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Another study of 2,798 peritoneal dialysis cases found that patients with HbA 1c ≥ 8.0% (63 mmol/mol) had higher all-cause mortality, but the study also noted that HbA 1c was vulnerable to albumin, inflammation, and hemoglobin [ 5 ]. About the variability of HbA 1c and the prognosis of dialysis patients, Afghahi H, et al [ 17 ] demonstrated that the inflation risk of all-cause mortality in peritoneal dialysis patients with diabetes was prominently connected with the increase of CV in HbA 1c , which is consistent with our conclusion, but 48.9% of the patients included in their study were measured only twice, and it would weaken the accuracy of CV.…”
Section: Discussionsupporting
confidence: 90%
“…Another study of 2,798 peritoneal dialysis cases found that patients with HbA 1c ≥ 8.0% (63 mmol/mol) had higher all-cause mortality, but the study also noted that HbA 1c was vulnerable to albumin, inflammation, and hemoglobin [ 5 ]. About the variability of HbA 1c and the prognosis of dialysis patients, Afghahi H, et al [ 17 ] demonstrated that the inflation risk of all-cause mortality in peritoneal dialysis patients with diabetes was prominently connected with the increase of CV in HbA 1c , which is consistent with our conclusion, but 48.9% of the patients included in their study were measured only twice, and it would weaken the accuracy of CV.…”
Section: Discussionsupporting
confidence: 90%
“…This is contradictory to the results of several studies, which have claimed that patients with diabetes mellitus did worse on PD than on HD [ 18 , 19 ], while favorable outcomes of PD were reported in patients without diabetes [ 10 , 20 ]. It was generally recognized in previous studies that PD therapy may affect blood glucose control in ESRD patients because the dialysate used for PD contains glucose [ 21 23 ], and diabetic patients are prone to developing disorders of lipid metabolism [ 24 ], which might accelerate the process of arteriosclerosis and increase the incidence of cardiovascular events [ 25 , 26 ]. There were also some studies that found no interactions between diabetes mellitus and initial modality concerning mortality [ 9 , 10 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is contradictory to the results of several studies, which have claimed that patients with diabetes mellitus did worse on PD than on HD [17,18], while favorable outcomes of PD were reported in patients without diabetes [10,19]. It was generally recognized in previous studies that PD therapy may affect blood glucose control in ESRD patients because the dialysate used for PD contains glucose [20][21][22], and diabetic patients are prone to developing disorders of lipid metabolism [23], which might accelerate the process of arteriosclerosis and increase the incidence of cardiovascular events [24,25]. There were also some studies that found no interactions between diabetes mellitus and initial modality concerning mortality [9,10,26].…”
mentioning
confidence: 89%